Osteonecrosis in Paediatric Patients with Acute Lymphoblastic Leukaemia Treated on Co-ALL-07-03 Trial: a Single Centre Analysis - Kuhlen, M.; Moldovan, A.; Krull, K.; Meisel, R.; Borkhardt, A. (Klinische Pädiatrie, 2014)
Background: Osteonecroses (ON) are a serious problem after anti-leukaemic treatment in childhood and critically depend on treatment intensity. We analysed ON incidence, risk factors and outcome in patients (pts) from our institution treated according to the CoALL 07-03 trial.Methods: Between 01.09.2003 and 31.12.2009, 124 children aged 1–18 years were treated, 22 pts with ON (ARCO I–IV) were assessed by retrospective chart review. Follow-up data were collected as of March 2013.Results: 5-year cumulative incidence of ON grade I–IV was 25%. Median age at ALL diagnosis with vs. without ON was 11 years vs. 4.4 years. In logistic multivariate regression analysis, age was the only independent risk factor for ON (p<0.01). 90.9% of the pts with ON presented with ≥2 bilaterally affected joints, most frequent the weight-bearing joints (95.5%). 77.2% developed ON ≥°III acc. to ARCO. 36.4% underwent core decompression, one patient bilateral total hip arthroplasty. As of March 2013, 12 pts still presented with ON-induced symptoms.Discussion: Our data suggest an overall high incidence of ON in pts treated according to trial CoALL 07-03. Cumulative steroid dose in trial CoALL 07-03 was small, thus, the high CI might be triggered by other treatment-related and study population based risk factors.Conclusion: ON are a serious problem concerning long-term sequelae with major impact on activities of daily living. Further prospective evaluation is urgently needed to develop risk-adapted diagnostic strategies and preventive and interventional approaches for high-risk pts.
Keywords: osteonecrosis; children; acute lymphoblastic leukaemia; incidence